(untitled) (Journal of Economic Research & Business Administration, 2024)
The importance of the research is highlighted by the special role of monotowns, which are closely monitored by the government as they face growing socio-economic issues while also playing a crucial role in the country’s economy. This article aims to develop and test a methodological approach to strategic marketing planning for establishing development priorities for monotowns in Kazakhstan. The study presents monotowns analyzed over different periods: 27, 20 and 9 monotowns of Kazakhstan. Current and future priorities for 9 monotowns are defined based on available statistical socio-economic indicators grouped by areas of territorial marketing. The research objectives include developing a methodological approach to strategic marketing planning, conducting typology, identifying the advantages and disadvantages of monotown development, creating a simulation modeling tool for socio-economic development using artificial intelligence technology, and determing strategic priorities development of monotowns. Data collection, processing, and analysis methods include content, comparative, factor, and cluster analysis, typology, and artificial intelligence modeling methods (supervised learning, error correction, BFGS optimization). The STATISTICA software version 13 was utilized for data analysis and forecasting. The results indicate that the strategic marketing planning tools developed are useful for establishing scientifically grounded development priorities for monotowns in Kazakhstan. This research is beneficial for government bodies aiming to devise socio-economic development strategies for monotowns. Key words: monotown, strategic marketing planning, typology, development priorities, factor analysis, cluster analysis, simulation modeling.